Fluorine-18: an untapped resource in inorganic chemistry. Issue 84 (7th September 2018) - Varlow, Cassis; Szames, Daniel; Dahl, Kenneth; Bernard-Gauthier, Vadim; Vasdev, Neil
Abstract : Advances in the field of fluorine chemistry have been applied extensively to the syntheses of 18 F-labelled organic compounds and radiopharmaceuticals. Abstract : Advances in the field of fluorine chemistry have been applied extensively to the syntheses of 18 F-labelled organic compounds and radiopharmaceuticals. However, 18 F has sparely been used as a tool to explore inorganic chemistry and can be viewed as a research area worthy of further development. This review highlights the application of 18 F in development of inorganic fluorinating agents, mechanistic studies and imaging tools.